Keberadaan Hukum Adat Jawa Dalam Perkawinan Modern - Eko, Febriyanto; Prasetio, Ilham Nur; Sofian, Robby (Lembaga Yasin AlSys, 2022)
Javanese traditional marriage is a form of syncretism of the influence of Hindu and Islamic customs. In Javanese tradition, offerings, calculations, taboos, and myths are still deeply rooted. Marriage according to the Javanese traditional community is a sincere love relationship between a young man and a woman which basically occurs because of frequent encounters between the two parties, namely a woman and a man. The Javanese proverb says